Fund Size, Fund Age dan Inflasi Sebagai Penentu Kinerja Reksadana - Wijayanti, Putu Yunita; Gama, Agus Wahyudi Salasa; Astiti, Ni Putu Yeni (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
The evaluation of the performance of mutual funds can define how competitive mutual funds are with other investment mutual funds on the market, thus it is crucial to pay attention to this development. In order for mutual fund performance to rise steadily each year in the future, research on the variables that can make them more competitive must be conducted. This study aimed to investigate the impact of inflation, fund age, and fund size variables on Indonesian mutual fund performance from 2018 to 2021. Equity funds operating in Indonesia and registered with the Financial Services Authority between 2018 and 2021 made up the study's sample. In this study, a sample of 30 equity funds was obtained through purposive sampling. Multiple linear regression analysis was employed for the study's data analysis. The findings of this study suggest that fund size influences mutual fund performance favourably. According to this study, a mutual fund's age has no bearing on how well it performs. The performance of mutual funds is said to be negatively impacted by the inflation variable in this study.